A Comparative Efficiency Analysis of Islamic and Non Islamic Bank in Indonesia Using Financial Ratios - Ardantyo, Irham Fauzan; Faturohman, Taufik (Journal of Business and Management, 2015)
Abstract - Islamic Bank grow all over the world, with first existence of Islamic bank in Middle East in 1970s and continue to grow. According to Islamic Financial Services Board 2015, the industry’s assets are estimated to be worth USD1.87 trillion as at 2014 and total Islamic Banking asset worldwide is estimated to be worth USD 1.47 trillion as at 2014. The first sign of Indonesia Islamic Banking begin appeared in 1992 which is Bank Muamalat Indonesia and continue to develop. As the Banking Industry in Indonesia keep growing, the Bank have to maintain their efficiency performance. This research aims to find out the difference between Non Islamic and Islamic performance in term of efficiency using financial ratios. The data used in this research are balance sheet and income statement Non Islamic, Islamic Business Unit, and Islamic Bank in Indonesia that are available during period 2004 – 2014. The total observation in this research is 1537 bank-year.  Method used in this research are computation with financial ratios, descriptive statistic, and Mann-Whitney Test. The results from the descriptive analysis mean value of each ratios, Islamic Bank efficiency performance shows that in early years of this study were not as good as Non Islamic Bank. The result of this study can be used by Islamic Bank management to give empirical evidence to the public that efficiency of Islamic Bank can come up and compete with Non Islamic Bank. Hopefully, it can increase the market share in Indonesia. Keywords: Islamic banking, banking Industry, financial ratios, efficiency.